Ileal pouch-anal anastomosis; 18 years of experience and outcomes across two generations of surgeons at a tertiary center in Sweden. (3rd April 2022) - Hermanson, Maria; Bengtson, Jonas; Croix, Hanna de la; Lindholm, Elisabet; Block, Mattias
Abstract: Aim: Reconstructive surgery with ileal pouch-anal anastomosis (IPAA) is the standard procedure after colectomy in patients with Ulcerative Colitis (UC) and Familial Adenomatous Polyposis (FAP). It is of interest to understand how a generation shift of the surgeons performing IPAA has affected patients' outcomes. Method: All consecutive patients who underwent IPAA in the period 1999–2016 at Sahlgrenska University Hospital/Östra, Gothenburg, Sweden, were included. Surgeons representing two different generations performed the surgeries during this period. The following 6-year time periods were assigned for surgeries performed by: experienced surgeons (1999–2004; Period 1); the new generation of surgeons undergoing training (2005–2010; Period 2); and the new generation of experienced surgeons (2011–2016; Period 3). The primary endpoint was post-operative complications (Clavien-Dindo ≥3b), and the secondary endpoints were the functional outcome, failure of the pouch, and mortality. Logistic analyses of the results were performed. Results: Overall, 281 patients were included in the study. The rate of post-operative severe complications was lower in Period 1 [Odds Ratio (OR) 0.137; p = .01]. There was no difference in functional outcome between the groups. Conclusion: This study implicates that the risk of post-operative complications after IPAA is lower when the surgery is performed by a generation of more-experienced surgeons. This might support literature that concludes that surgical units that have a high throughput of patients and are staffed by surgeons who perform many procedures provide better outcomes.